Elevated Aβ42 in Aged, Non-demented Individuals with Cerebral Atherosclerosis - R. Sadleir, Katherine; A. Bennett, David; A. Schneider, Julie; Vassar, Robert (Current Alzheimer Research, 2013)
The β-secretase, BACE1, generates β-amyloid (Aβ), a major hallmark of Alzheimer's disease (AD) pathology. The elevation of BACE1 levels in brains of AD patients may play a role in initiating or propagating disease. BACE1 levels are increased under low energy or low oxygen conditions, which may occur in individuals with impaired circulation in the brain. We compared levels of BACE1 in the brains of aged, non-demented individuals with high or low levels of atherosclerosis in the circle of Willis, and found that while there is no change in BACE1, Aβ42 levels are elevated in the high atherosclerosis group.
Keywords: eIF2α